NECROTIZING FASCIITIS IN A UNUSUAL SITE: A CASE REPORT - Casimiro, Icrad; Freitas, Sabrina Ribas (Mastology, 2021)
Case Report: A 56-year-old woman, multiparous patient, diabetic, hypertensive and tabagist, and taking insulin, metformin, losartan, propranolol, hydrochlorothiazide, and aspirin presents to a clinic. She also had a previous surgery for extraction of a duodenum carcinoma and a nodule in lower lateral quadrant of right breast about 15 years ago, which on previous ultrasound was hyperechoic, with heterogeneous content, measuring about 27×18.5×25 mm. Upon arrival at the hospital, the patient had an ulcerated lesion with a central necrotic area in the lower outer quadrant of the right breast, with drainage of bloody secretion and a foul odor, and a generalized hyperemia in the region of the right breast. On physical examination, the patient had local hyperemia and areas of fluctuation in lateral quadrants. There were no palpable lymph nodes. The results of her initial laboratory investigations showed a leukocytosis and an increased erythrocyte sedimentation rate and C-reactive protein. A computed tomography scan of the breast, chest, and abdomen showed massive subcutaneous emphysema in the right breast, extending from the subcutaneous region of the anterolateral and abdominal chest wall to the right iliac fossa, associated with diffuse densification of the muscular fascia and adjacent subcutaneous tissue. She was treated with intravenous broad-spectrum antibiotics that included 1 g of oxacillin and 1.5 g of metronidazole. She underwent surgical debridement for 3 consecutive days, starting 24 hours after hospital admission. She was recommended 1 g of ceftriaxone and amphotericin B along with antibiotic therapy. At the second surgery, a wound tissue was collected for histopathological examination discarding malignancy. Five weeks later, wounds appeared clean, healing with pink granulation tissue. Conclusion: This case shows that early diagnosis and management of necrotizing fasciitis of the breast can be lifesaving and may allow for breast conservation. Early aggressive debridement combined with antibiotic therapy resulted in successful wound healing and preservation of tissue with a satisfactory cosmetic outcome.